Efektivitas Media Pembelajaran Pendidikan Agama Islam (PAI) Berbasis Sparkol Videoscribe - Arip Febrianto; Nurirwan Saputra (Jurnal Dinamika Informatika, 2020)
In the subject of Pendidikan Agama Islam (PAI), most of the material istheoretical and the deepening of the material includes analyzing something basedon Islamic Vision by conveying the material and basic learning then studentsanalyze the problems encountered. With the development of InformationTechnology, teacher using information technology in learning delivered to students.Based on what has been done, students tend to be less interested in receivingPAI learning. In this study, audio-visual learning media was used by utilizing theSparkol videoscribe application. Through the Videoscribe application, the teachercreated learning in the form of interactive Audio Visual Animations with students.Based on the learning carried out using Videoscribe media, 83.3% ofstudents prefer learning with videoscribe compared to text-based only, 58.3% areinterested and 41.7% are very interested in learning using this videoscribe.